(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The history of Indian Freedom Movement would beincomplete without mentioning the contributions of women. The sacrifices madeby the women of India will occupy the foremost place. They fought with truespirit and undaunted courage and faced various tortures, exploitations andhardships to earn us freedom. Swadeshi movement was one of the major events in theHistory of Indian FreedomMovement. It was started in 1905 as an agitationagainst the partition of Bengal and it spreadto other parts of the countryincluding Maharashtra. The Slogans of Swaraj, the concepts of boycott, NationalEducation and the spirit of Swadeshi were spread from Bengal toMaharashtraalong with other regions.